MgB2 superconducting joints for persistent current operation. (7th May 2015) - Patel, Dipak; Al Hossain, Md Shahriar; Wai See, Khay; Xu, Xun; Barua, Shaon; Ma, Zongqing; Choi, Seyong; Tomsic, Mike; Ho Kim, Jung
Abstract: High-performance superconducting joints are essential for realizing persistent-mode magnets. Herein, we propose a concept and fabrication of such superconducting joints, which yielded reliable performance in the operating temperature range of 4.2–25 K. MgB2 –MgB2 joints in magnets are known to result in deterioration of localized electrical, thermal, and mechanical properties. To overcome these problems, the ends of the two wires are inserted into a pellet press, which is then filled with a mixture of unreacted magnesium and boron powders, followed by heat treatment. The critical current capacity and joint resistance were precisely evaluated by the standard four-probe method in open-circuit and by field-decay measurements in a closed-loop, respectively. These joints demonstrated up to 66% of the current-carrying capacity of unjoined wire at 20 K, 2 T and joint resistance of 1.4 × 10 −12 Ω at 4.2 K in self-field.